Determinan Pola Asuh Orang Tua pada Anak Usia Pra Sekolah di Era New Normal - Monalisa Monalisa; Loriza Sativa Yan; Nur Fadilla Bahri (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the determinants of parenting style for preschool-age children in the new average era in the Kenali Besar Public Health Center, Jambi City, working area. This research method is quantitative research with a cross-sectional research design. The results showed that most parents' upbringing was good, 53 people (54.2%), while the poor category was 43 (44.8%). The bivariate analysis results showed that the p-value between parenting style and age, education, and income was 0.000. In conclusion, parenting style in the new average period is related to age, education, and high income. Keywords: New Normal, Parenting Style, Preschool Age